VARIATIONS IN THE MINERAL CONCENTRATION AMONG DIFFERENT POTATO (SOLANUM TUBEROSUM L.) ACCESSIONS - Singh, Baljeet; Sharma, Jagdev; Bhardwaj, Vinay; Sood, Salej; Siddappa, Sundaresha; Goutam, Umesh; Dalamu, Dalamu; Kardile, Hemant; Dipta, Bhawna; Pandey, NK (Potato Journal, 2022)
A collection of one hundred tetraploid potato accessions was evaluated in relation to the concentrationsof nine minerals (Fe, Zn, Cu, Mn, Ca, Mg, S, P and K) required for human nutrition. Large amount of variability forselected minerals was observed in the germplasm. Significant positive correlations (P < 0.001) were found between Fe-Cu (r2=0.41), Zn-Cu (r2=0.46), Mn-K (r2=0.51) and Ca-Mg (r2=0.40), whereas significant negative correlation (P < 0.001) wasobserved between P-K (r2= -0.36). The first two principle components accounted 42.72% of the total observed variations.Unweighted pair group method with arithmetic mean (UPGMA) based clustering distinguished the potato accessions intodifferent groups based on Gower distances. These results will be useful for developing biofortified potato varieties usingtraditional and modern breeding methods. Moreover, variations in the mineral contents within the potato germplasmcould also be used for the identification of molecular markers associated with mineral concentrations through genomewide association studies (GWAS).